The Influence of Agroclimate, Gandatapa Village, Sumbang Subdistrict on Microbial Profile, Brix Values, and Total Sugar, Naturally Spread Coconut Sap - Gunawan Wijonarko; Ike Sitoresmi Mulyo Purbowati; Tatang Widjojoko; Ali Maksum (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2022)
Temperature and relative humidity are factors that affect the microbial profile and brix value of coconut sap. High temperature and relative humidity tend to support microbial growth. On the other hand, high relative humidity will reduce the brix value and total coconut sap sugar. Therefore, it is necessary to study the relationship between agro-climatic conditions with microbial profile, brix value and total sugar in organically run coconut sap in Gandatapa Village. This research is expected to provide benefits for those who need coconut sap as a source of S. cerevisiae and as a raw material for the manufacture of brown sugar. Coconut sap samples were taken using a simple random technique. Temperature and relative humidity were recorded for each sampling. 250 ml of coconut sap was put into a sterile plastic bottle and then using an ice box, it was taken to the Agricultural Technology Laboratory for analysis. The analysis carried out included total microbes, total yeast, total bacteria, yeast percentage, brix value and total coconut sap sugar. The data were analyzed using Pearson correlation to determine the relationship and the degree of closeness. The results showed that temperature and relative humidity were positively correlated with the microbial profile of organically dissolved coconut sap. At an air temperature of 28.4oC and an air humidity of 81%, the total microbes of organically run coconut sap were 6.45 logs, the total yeast was 4.28 log cfu/ml, the total bacteria were 2.52 log cfu/ml and the yeast percentage was 72, 75%. Brix values ​​and total sugar under the same conditions were 16.7% and 8.25%. The value of brix and total sugar of coconut sap is negatively correlated with temperature and relative humidity. There is a strong relationship between temperature and total microbial, brix value and total sugar. The correlation coefficient is 0.71, respectively; -0.81 and -0.78. Strong correlations were also observed between relative humidity and total microbial, total yeast and brix values. The correlation coefficient is 0.85, respectively; 0.82; and -0.83.